Broken mirrors = Sinalcol - Ḫūrī, Ilyās 1948-2024 (Archipelago Books, 2015)
"Karim Chammas returns to Lebanon, his family, and his past after ten years of establishing a new life in France. Back in Beirut, Karim reacquaints himself with his brother Nassim, now married to his former love Hind, and old friends from the leftist political circles within which he once roamed under the nom de guerre Sinalcol. By the end of his six-month stay, he has been reintroduced to the chaos of cultural, religious and political battles that continue to rage in Lebanon. Overwhelmed by the experiences of his return, Karim is forced to contemplate his identity and his place in Lebanon's history. The story of Karim and his family is born of other stories that intertwine to form an imposing fresco of Lebanese society over the past fifty years. Broken Mirrors examines the roots of an endemic civil war and a country's unsettled past"...